Решите квадратные уравнения 2×2+9x+4=0, 1/6×2-13x/6+7=0, 2 целых 1/3 x2 — 3целых 1/2x=0

решите квадратные уравнения 2x2+9x+4=0, 1/6x2-13x/6+7=0, 2 целых 1/3 x2 - 3целых 1/2x=0

    x1=(7-9)/(2*2)=--2/4=-0.5
    x2=(-7-9)/(2*2)=-16/4=-4

     

    (7/3)*x^2-3.5*x=0

    D=(-3.5)^2-4*(7//3)*0=12.25-(28/3)*0=12.25;

  • 2x^2+9x+4=0

    D=(-13/6)^2-4*(1/6)*7=(169/36)-(14/3)=1/36

    1/6x^2-13x/6+7=0

    2 1/3x^2-3 1/2x=0

    x1=(3.5-(-3.5))/(2*(7/3))=7/(14/3)=1.5
    x2=(-3.5-(-3.5))/(2*(7/3))=0/(14/3)=0

  • D=9^2-4*2*4=81-32=49

    x1=((1/6)-(-(13/6)))/(2*(1/6))=(7/3)/(1/3)=7
    x2=(-(1/6)-(-(13/6)))/(2*(1/6))=2/(1/3)=6